NPK fertilization effects on soil fertility, mineral nutrition and growth of rubber trees - Bataglia O C; Santos W R (Revista Brasileira de Ciencia do Solo, 1999)
The soil and plant responses to a continuous supply of NPK fertilizers on rubber trees, clone RRIM 600, was studied in an experiment on a red-yellow podzolic soil of sand/medium texture in Sao Paulo State, Brazil. A fractionated factorial experiment 1/2 (4x4x4) was used, with doses of 0, 40, 80 and 120 kg ha-1 of N, P2O5 and K2O, applied as urea, triple superphosphate and potassium chloride. The evaluations consisted of soil, leaf and trunk girth analyses. The nitrogen fertilizer (urea) promoted the greatest changes in soil fertility, significantly increasing soil acidity. Leaf N concentration was enhanced while K and S decreaed. Phosphate fertilizer increased soil P availability and leaf P. Potassium fertilizer improved soil and leaf K contents. Leaf N was better correlated with plant growth while soil and leaf P and K were not consistently correlated. Boron concentrations in the leaves were positively correlated with the immaturity period of the crop. The availability of other micronutrients was not affected by the fertilizer treatments. Nitrogen and potassium nutrition showed the best correlations with crop growth. Differences up to twelve months in the immaturity period were observed for the different treatments.
Source Year: 2000
Keywords: Growth; Mineral nutrition; NPK fertilization; Soil fertility